Evaluation of hypoglycemic and anti-hyperglycemic potential of Tridax procumbens (Linn.) - Jain Kusum; Khajja Balvant S; Sharma Sameer; Pareek Hemant; Jain GC (BMC, 2009)
Abstract Background Diabetes is a metabolic disorder affecting carbohydrate, fat and protein metabolism. Tridax procumbens Linn. (Family-Asteraceae; common name-Dhaman grass) is common herb found in India. Traditionally, the tribal inhabitants of Udaipur district in Rajasthan (India) uses the leaf powder (along with other herb) orally to treat diabetes. There is a need to evaluate extracts of this plant in order to provide scientific proof for it's application in traditional medicine system. Methods Extraction of whole plant of T. procumbens using 50%methanol. The extract was tested for acute and sub-chronic anti-hyperglycemic activity in alloxan induced diabetic rats and for acute toxicity test among normal rats. Observations on body weight as well as on the oral glucose tolerance levels were also recorded. Results Oral administration of acute and sub chronic doses (250 and 500 mg/kg b.wt.) of T. procumbens extract showed a significant (p < 0.05) reduction in fasting blood glucose levels in diabetic rats, however the decline in blood sugar levels in normal rats was not observed. In acute study the maximum percent blood glucose reduction (68.26% at 250 mg/kg and 71.03% at 500 mg/kg body weight) in diabetic rats was observed at 6 h. The anti-hyperglycemic effects were not dependent of dose and the OGTT and Body weight supported the antihyperglycemic action of the drug. The results of anti-diabetic effect of T. procumbens were compared with the reference standard drug Glibenclamide (10 mg/kg b.wt.). Conclusion These test results support traditional medicinal use of, T. procumbens for the treatment of diabetes mellitus with corrections in body weight and oral glucose tolerance and no visible signs or symptoms of toxicity in normal rats indicating a high margin of safety. These results warrant follow-up through bioassay-directed isolation of the active principles.